Can auditory-based intervention enhance the motor learning of novice hurdlers? - Tan, Clenyce Zi Xin (Nanyang Technological University, 2021)
Movement sonification is a type of auditory feedback which holds much potential for enhancing motor learning. However, sonification design is complex and only effective if well-customized to the individual and movement context. This study was conducted to find out if presenting music or metronome beats between hurdling attempts would affect the motor learning of novice learners measured by hurdle cadence. 12 healthy young adults (6M/6F, 21-40 years old) who were new to audio-motor synchronization training and hurdling were recruited and divided equally into groups for the training session – either listening to white noise as controls or auditory feedback (metronome beats or music) that was 10% faster than their natural cadence between hurdles. The training session was held between a pre-test and post-test scheduled a minimum of 48 hours apart, with a retention test held 3 weeks after the post-test. Each session, participants completed a set number of runs through a fixed hurdle setup in an indoor sports hall. Their step cadence between hurdles was video recorded during the pre-test, post-test and retention test. Repeated measures analysis of variance revealed that all participants exhibited significantly faster cadence between hurdles, F(2,18) = 6.67, p = .007, ηp2 = .43. Bonferroni post-hoc analysis highlighted that cadence was significantly faster (p = .045) during the retention test compared to the pre-test. No other significant variation in means were observed across different feedback conditions. Findings suggest that novice learners increased hurdle cadence quickly over time, with no significant effect of auditory feedback presented.